Mandibular movements in children with and without signs and symptoms of temporomandibular disorders Movimentos mandibulares em crianças portadoras ou não de sinais e sintomas de disfunção temporomandibular - Leonardo Rigoldi Bonjardim; Maria Beatriz Duarte Gavião; Luciano José Pereira; Paula Midori Castelo (University of São Paulo, 2004)
This research aimed to evaluate mandibular movements in children with and without signs and symptoms of temporomandibular dysfunction. The sample taken consisted of 99 children aged 3 to 5 years distributed in two groups: I - Absence of signs and/or symptoms of TMD (25 girls/40 boys); II - Presence of signs and symptoms of TMD (16 girls/18 boys). The symptoms were evaluated through an anamnesis questionnaire answered by the child's parents/caretakers. The clinical signs were evaluated through intra- and extraoral examination. Maximum mouth opening and left/right lateral movements were measured using a digital caliper. The maximum protrusive movement was measured using a millimeter ruler. The means and standard deviations for maximum mouth opening in Group I and Group II were 40.82mm±4.18 and 40.46mm±6.66, respectively. The values found for the left lateral movement were 6.96mm±1.66 for Group I and 6.74mm±1.55 for Group II, while for the right lateral movement they were 6.46mm±1.53 and 6.74mm±1.77. The maximum protrusion movements were 5.67mm±1.76 and 6.12mm±1.92, in Groups I and II, respectively. The mandibular movement ranges neither differed statistically between groups nor between genders. FAPESP Process 96/0714-6. O objetivo desta pesquisa foi avaliar a amplitude dos movimentos mandibulares em crianças portadoras ou não de sinais e sintomas de disfunção temporomandibular. A amostra consistiu de 99 crianças entre 3 e 5 anos distribuídas em 2 grupos: I - Ausência de sinais e sintomas de DTM (25 meninas/40 meninos) II - Presença de sinais e sintomas de DTM (16 meninas/18 meninos). Os sintomas foram avaliados através de um questionário respondido pelos pais ou responsáveis das crianças. Os sinais clínicos foram avaliados através de exame intra e extra-oral por dois examinadores calibrados. Os movimentos de abertura máxima e lateralidade direita e esquerda foram mensurados com o auxílio de um paquímetro digital. Para o movimento de protrusão foi utilizada régua milimetrada. A média e o desvio padrão para abertura bucal máxima para o grupo I foi de 40,82mm±4,18 e para o grupo II 40,46mm±6,66. Os valores encontrados para a lateralidade esquerda foram 6,96mm±1,66 para o grupo I e 6,74mm±1,55 para o grupo II e, para a direita, foram 6,46mm±1,53 e de 6,74mm±1,77, respectivamente. Durante a protrusão foram encontrados valores de 5,67mm±1,76 para o grupo I e 6,12mm±1,92 para grupo II. Pode-se concluir que na amostra avaliada a amplitude dos movimentos mandibulares não diferiu estatisticamente entre os grupos, bem como entre os gêneros. FAPESP Processo 96/0714-6.